Educational uses of ICT in rural teachers in Colombia - Uribe-Zapata, Alejandro; Zambrano-Acosta, Juan Fernando; Cano-Vásquez, Lina María (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The present article discussed the educational uses of ICT in rural teachers in Colombia. A quantitative design and an instrument that addressed the following were used: characterization, private connectivity, pedagogical use of mobile phones and the internet in teaching practice, mobile phones and internet in the classroom, and level of ICT skills. The sample consisted of a total of 241 rural teachers from the department of Antioquia, Colombia. The results show that the majority of rural teachers are between 31 and 45 years old, that they are women, that the level in terms of postgraduate training is low, that the use of mobile devices is practically universal, that there is a greater educational use of ICT for the management of teaching during planning and less in the evaluation and that the majority of rural teachers are at the explorer level.